Real-world data of thrombotic microangiopathy management: The key role of ADAMTS13 activity and complement testing - Eleni Gavriilaki; Eudoxia-Evaggelia Koravou; Thomas Chatziconstantinou; Christina Kalpadaki; Nikoleta Printza; Maria Ximeri; Anna Christoforidou; George Karavalakis; Maria Kaliou; Vassiliki Kalaitzidou; Iliana Tassi; Maria Tzellou; et al. (Thrombosis Update, 2021)
ADAMTS13 (A Disintegrin and Metalloprotease with ThromboSpondin type 1 motifs) activity is a key tool in differential diagnosis of thrombotic microangiopathies (TMAs). Due to the lack of availability of ADAMTS13 testing, PLASMIC/PLASIC scores have been suggested to predict ADAMTS13 deficiency. The importance of differentiating TTP from other complement-mediated TMAs is highlighted by the need to urgently start plasma exchange and utility of treatments such as caplacizumab or eculuzimab. Therefore, we aimed to evaluate ADAMTS13 activity, PLASMIC/PLASIC scores, and complement testing in guiding management of a real-world TMA cohort. We enrolled consecutive TMA patients with samples referred to our Center (01/2018–2020). If ADAMTS13 ​> ​10%, soluble C5b-9 was measured. Among 80 TMA patients, ADAMTS13 activity was ≤10% in 50 patients, while 28 had a relapsing disease. PLASMIC/PLASIC were excellent predictors of ADAMTS13 deficiency, especially in patients without secondary causes. Soluble C5b-9 levels were elevated (median 525 ​ng/ml, range 313–913 ​ng/ml) in 7 patients without secondary causes and ADAMTS13 ​> ​10% (hemolytic uremic syndrome/HUS). Two were shiga-toxin associated; while 5 atypical HUS. Only 1/5 patients received eculizumab and achieved TMA resolution implemented by guidance based on soluble C5b-9 levels. In transplant-associated TMA, 8/16 patients not responding to first-line treatment received eculizumab due to elevated C5b-9 levels (median 353 ​ng/ml, range 281–1252 ​ng/ml) and achieved TMA resolution. In conclusion, our real-world data confirm that ADAMTS13, complement testing, and PLASMIC/PLASIC are valuable tools in diagnosis and management of TMAs, but also highlight the unmet need of using available markers and treatments in clinical practice.